INTERFERENSI BAHASA BUGIS, ARAB, DAN INGGRIS TERHADAP BAHASA INDONESIA PADA MAHASISWA IAIN PAREPARE: KAJIAN SOSIOLINGUISTIK - Suhartina (Jurnal Semantik, 2024)
This research aims to describe the forms of interference from Arabic, English, and Bugis languages into Indonesian, as well as the causes of such interference. This study employs a qualitative method with semi-structured interview techniques, text analysis, and observation. The theories used in this research are sociolinguistic theory, which views language as a social and cultural phenomenon, and language contact theory, which explains that bilingualism can lead to language interference. The results show that the interference from Bugis, English, and Arabic into Indonesian among students includes phonological, lexical, and morphological interference. The causes of language interference among students are bilingualism, lack of knowledge, habits, and politeness.